Together We Stand, Divided We Fall : Levels and Determinants of Social Capital in Argentina - World Bank (Washington, DC, 2013)
The study looks at recent analytical work concerning social issues in Argentina, which suggest both inequality, and unemployment are worsening, aggravated by pessimism and despair - partly shaped by a recession of almost three years - as well as by the inadequacy of public institutions. This study examines the case of Argentina, and draws on its existing social capital as an immediate strategy, and an investment for the future, to assess the role social capital can play within its context. The study finds that aggregate levels of social capital in Argentina are low, outlining that while the social capital of the poor in the country, may enable protection among themselves in times of hardship, it does not help them get ahead in the long-term. Civic associations have proved vulnerable to deep changes in the local social, economic, and political landscape, seemingly due to a historic heritage of authoritarian relations with the state. Thus, the study attempts to promote a dialogue among national actors, and policy makers on the implications of the determinants of social participation, and interpersonal trust. Evidence suggests that less than twenty percent of the population participates in any form of organization, of which, determinants of participation feature the better off, higher educated, or unemployed, while the poorest tend to find the experience unrewarding. The study also measures levels of less structured collective action in response to shocks, as a strategy for interacting with public officials, pointing out that during any form of crisis, Argentines turn to their closest circles of family, or friends, but do not assert their influence on public decisions during prosperous times. Recommendations suggest the creation of an enabling climate for the development of social capital, that provides space for public-private interactions, emphasizing on educational investments, and, creating a culture of information dissemination, and transparency.